SYNTROPIC AND ASSOCIATED COMORBID LESIONS OF THE CARDIOVASCULAR SYSTEM IN PATIENTS WITH LIVER CIRRHOSIS - Abrahamovych, O.O.; Abrahamovych, M.O.; Farmaha, M.L.; Leshchuk, Y.L.; Tsyhanyk, L.V.; Farmaha, T.I.; Leshchuk, Y.S. (World of Medicine and Biology, 2022)
Liver cirrhosis is a common disease occurring mainly among people of working age and frequently resulting in lethal outcomes. The causes of such epidemiology of liver cirrhosis are syntropic comorbid lesions, in particular lesions of the circulatory system organs. The study was carried out in three consecutive steps, namely: in the first phase the proportion of patients with liver cirrhosis with extrahepatic cardiovascular lesions was revealed, in the second, the frequency of each individual cardiovascular disease in patients was evaluated, and in the third phase the frequency of cardiovascular system lesions in every severity class of liver cirrhosis in accordance with C.G. Child-R.N. Pugh criteria and correlation between their incidence and class of cirrhosis were revealed. 81.3 % of patients with liver cirrhosis have lesions of the circulatory system, among which cirrhotic cardiomyopathy and disorders in the system of blood pressure regulation with the emergence of persistent arterial hypotension have common pathogenetic mechanisms with liver cirrhosis, namely, they are syntropic, whilst postinfarction cardiosclerosis, angina pectoris, acquired heart defects, and painless form of coronary heart disease are concomitant.
Keywords: liver cirrhosis; cardiomyopathy; arterial hypertension; syntropic lesions